The psychological effects of event cancellation in Olympic-level swimmers: preliminary findings and mental health screening recommendations - Hooper, N. R.; Reiber, C.; Cheatham, S. A. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Mental health screening of elite athletes is not routinely practiced following the cancellation of an athletic event. Though sporting event cancellation has negative career and training impacts on elite athletes, little is known about its psychological impact. To determine the extent to which sporting event cancellation might warrant psychological screening practices in elite athletics, this study evaluated elite-level swimmers` response to the cancellation of the 2020 Olympic Games through psychological assessment and qualitative interviewing. METHODS: A cross-sectional study design was implemented. Online psychological assessment included self-report scales to measure anxiety, burnout, psychological strain, and optimism/pessimism. Follow-up semistructured telehealth interviews were conducted to assess appraisals of and coping responses to the cancellation. RESULTS: Of the 14 participants assessed for mental health symptoms, 12 were available for interview procedures. Results (mean±SD) indicated "very high" psychological strain (22.71±4.83) and "mild" anxiety (6.29±4.87). All swimmers exhibited levels of psychological strain that warranted clinical evaluation per established cut-off scores. Thematic content analysis of interviews generated four themes: precancellation evaluations, primary appraisals, coping responses, and coping outcomes. Most swimmers exhibited maladaptive coping (75%); however, adaptative coping was as prevalent (92%), particularly through use of support networks. Most swimmers achieved positive coping outcomes (75%) and maintained strong 2021 Olympic-qualifying confidence (93%). In contrast, swimmers with poor coping outcomes (25%) employed more frequent maladaptive coping strategies and exhibited higher psychological distress. CONCLUSIONS: Findings urge sports medicine clinicians to implement psychological screening protocols in elite athletes following the cancellation of a major sporting event to attend to symptoms of psychological distress and to direct appropriate psychological intervention.